Forest structure and biodiversity patterns along elevational gradients in eastern Nepal - Gachhadar, Pramila Kumari; Mandal, Tej Narayan; Baniya, Chitra Bahadur (Scientific World, 2023)
This study aimed to assess the forest structure, composition, and diversity pattern at different elevations in Morang District, eastern Nepal, using stratified random vegetation sampling technique in five forests: Bhaunne, Raja-Rani, Murchungi, Adheri, and Sagma. Trees, shrubs and herbs of each forest was sampled through quadrat of 20 × 20 m2, 5 × 5 m2, and 1 × 1 m2 each respectively. A total of 315 plant species belonging to 82 families and 255 genera found by this study. A total of 50 quadrats each for trees, shrubs and herbs sampled during this study. A total 10 quadrats studied for each life form from each forest. This study obtained 5,037 individuals across all forests. The highest number of species (55) was recorded from Raja Rani forest, and the highest tree density (985 ind ha-1) was observed in Adheri forest. The highest density of shrub (24400 ind. ha-1) and herbs (44.1 ind.m-2) were recorded in Sagma forest. The Shannon Wiener index value of herb layer was found to be the highest (3.79) at Bhaunne forest. This value for shrub layer was 2.98 and tree layer was 3.12 at Sagma which was the maximum among forests. The concentrations of dominance value were high for herb and shrub layer in Bhaunne forest, and it was maximum for the tree layer in Adheri forest. The forest species composition were significantly different (p ≤ 0.001) among each other. Total basal area of shrub layer and tree layer recorded were maximum (111.52 m2 ha-1 and 612.08 m2 ha-1) in Sagma and Adheri forest, respectively. The number of trees decreased with increasing elevation, while shrubs increased, and herbs showed a U-shaped trend. The dominant tree species were Senegalia catechu, Shorea robusta, Terminalia alata, and Schima wallichii in Bhaunne, Raja-Rani, Murchungi, and Sagma forest, respectively, with Shorea robusta being dominant in Adheri forest. These findings have important implications for forest management and conservation efforts in the region.